A 610-mW zero-overhead class-G full-rate ADSL CO line driver. - Maclean, K. (IEEE Journal of solid state circuits)
With the drive to increase the number of ports that can be incorporated onto a single linecard in an ADSL Central Office (CO), and the consequent power consumption and thermal management issues that this increased density raises, power dissipation is a key parameter in the design of an ADSL modem. This paper presents a full-rate ADSL CO line driver, consuming 610 mW through active termination and a zero-overhead class-G technique. The supply switching scheme used features very low overhead voltage, logic control, and controlled supply rail ramp rate, and requires analog signal peak prediction be done on the digital data stream. The process used features dielectrically isolated silicon-on-insulator 0.7-μm complementary BiCMOS with thin-film resistors. The MOSFET class-G transistors operate in two modes for power efficiency and distortion control. The power consumption is 610 mW and the downstream missing tone power ratio is 69 dBC with 16-dB peak-to-average ratio support.